ANALISIS WACANA FEMINISME SARA MILLS PROGRAM TUPPERWARE SHE CAN! ON RADIO (Studi Kasus Pada Radio Female Semarang) - Septyan Widya Wardani; Daru Purnomo; John R Lahade (Cakrawala Jurnal Penelitian Sosial, 2013)
Mass media has a big role in forming and changing society’s mind, feeling, attitude, opinion and behavior about women. However, women representation in mass media still shows negative stereotype. The existence of radio stations with female target audience which is aimed to empower women is a new hope for women related with the formation for positive image of women through the programs. Female Radio Semarang became one of the radio with female target audience who helped take the role in the formation of positive image of women through a program called Tupperware She Can! on Radio. All of their efforts are absolutely not separated from Female Radio Semarang ideology as a mass media based on gender perspective. This research will analyze how the discourse strategies that apply in the Tupperware She Can! on Radio in representing women. The type and the approaches of this research is a qualitative-descriptive methods with critical discourse analysis method which developed by Sara Mills, which is also often referred to as critical discourse analysis with ‘feminist’ perspective. By analyzing the transcript of the Tupperware She Can! on Radio, using Sara Mills theory on the subject-object position and the listener’s position, this study aims to describe the discourse strategies that apply in the Tupperware She Can! on Radio in representing women.The result of this thesis research shows that Female Radio Semarang through its program Tupperware She Can! on Radio has been trying to represent women positively. In the course Tupperware She Can! on Radio, women are not only positioned as the object but also given a lot opportunity to become the subject of conversation. As a result, the women representation that formed in the program showed a positive image. In the lead of role in the public sector (productive or social), women appear as a figure no less with men, yet in the domestic sector women still perform her responsibilities for carrying out her role as mother and wife as well. Keywords : Representation, Women, Discource Analysis, Program Tupperware She Can! on Radio